DESCRIPTION OF HUSBAND'S SUPPORT AND EMPLOYMENT STATUS WITH THE INCIDENCE OF ANEMIA IN PREGNANT WOMEN IN JORONG KAJA KOTO BARU - Fany, Fiona (Universitas Fort De Kock, 2025)
Introduction: During pregnancy, the occurrence of anemia is one of the main health problems that is still often found in pregnancy, including in the Jorong Kajai area, Koto Baru. Based on the results of a study on the causes of MMR in Solok Regency in 2022, anemia in pregnancy was identified as one of the factors contributing to the increased risk of maternal mortality. Factors that influence the incidence of anemia in pregnant women include the level of support from the husband and the mother's employment status. Support from the husband has been shown to have a positive influence on the motivation of pregnant women in maintaining the health of their pregnancy. Employment status also affects pregnant women where pregnant women who do not work pay more attention to their pregnancy. Objective: To see an overview of husband support and employment status for pregnant women. Method: Descriptive with a cross-sectional approach with a total sampling number of 36 people. Results: shows the incidence of anemia in pregnant women who do not receive support from their husbands, and do not work in Jorong Kajai Koto Baru Solok in 2024.